Pemanfaatan Manajemen Teknologi Informasi Untuk Strategi dan Perencanaan - Herru Soerjono (TEMATIK, 2023)
The use of information technology management has a positive effect on reducing management costs, improving management quality, facilitating communication between managers, and saving time and quality of communication within the company. Strategy for utilizing information technology management by speeding up services to market needs for services from the latest information technology. Planning the utilization of information technology management can reduce the risk of disruption to data and information security. Recovery planning from data and information security disruptions must contain information that enables information technology management to ensure the organization's ability to continue critical computing and telecommunications services and operations. The policy for utilizing information technology management includes, among other things, providing information technology services so as to provide satisfaction to customers. A successful information technology management structure must have a solid set of processes for interacting and communicating with customers. By establishing good relationships with customers, information technology organizations can improve all forms of customer interactions including translating customer requests into solutions, providing service and support, and accessing customer satisfaction. The results and discussion in this research are that the use of information technology management through management information systems will provide benefits in increasing the efficiency and effectiveness of business activities, especially in the management process and business decision making.